theorem sabssxped (A C: set) (G: wff) (a: nat) (p: wff) {x: nat} (B: set x): $ G /\ x = fst a -> snd a e. B -> p /\ x e. A /\ snd a e. C $ > $ G -> a e. S\ x, B -> p /\ a e. Xp A C $;
Step | Hyp | Ref | Expression |
---|---|---|---|
2 |
fst a, snd a e. S\ x, B <-> snd a e. S[fst a / x] B |
||
5 |
fst a, snd a = a |
||
6 |
fst a, snd a e. S\ x, B <-> a e. S\ x, B |
||
7 |
snd a e. S[fst a / x] B <-> a e. S\ x, B |
||
8 |
a e. Xp A C <-> fst a e. A /\ snd a e. C |
||
9 |
p /\ a e. Xp A C <-> p /\ (fst a e. A /\ snd a e. C) |
||
10 |
E. x x = fst a |
||
11 |
F/ x G |
||
12 |
FS/ x S[fst a / x] B |
||
13 |
F/ x snd a e. S[fst a / x] B |
||
14 |
F/ x p /\ (fst a e. A /\ snd a e. C) |
||
15 |
F/ x snd a e. S[fst a / x] B -> p /\ (fst a e. A /\ snd a e. C) |
||
16 |
x = fst a -> B == S[fst a / x] B |
||
17 |
x = fst a -> (snd a e. B <-> snd a e. S[fst a / x] B) |
||
18 |
p /\ fst a e. A /\ snd a e. C <-> p /\ (fst a e. A /\ snd a e. C) |
||
19 |
x = fst a -> (x e. A <-> fst a e. A) |
||
20 |
x = fst a -> (p /\ x e. A <-> p /\ fst a e. A) |
||
21 |
x = fst a -> (p /\ x e. A /\ snd a e. C <-> p /\ fst a e. A /\ snd a e. C) |
||
22 |
x = fst a -> (p /\ x e. A /\ snd a e. C <-> p /\ (fst a e. A /\ snd a e. C)) |
||
23 |
x = fst a -> (snd a e. B -> p /\ x e. A /\ snd a e. C <-> snd a e. S[fst a / x] B -> p /\ (fst a e. A /\ snd a e. C)) |
||
24 |
G /\ x = fst a -> (snd a e. B -> p /\ x e. A /\ snd a e. C <-> snd a e. S[fst a / x] B -> p /\ (fst a e. A /\ snd a e. C)) |
||
25 |
hyp h |
G /\ x = fst a -> snd a e. B -> p /\ x e. A /\ snd a e. C |
|
26 |
G /\ x = fst a -> snd a e. S[fst a / x] B -> p /\ (fst a e. A /\ snd a e. C) |
||
27 |
G -> x = fst a -> snd a e. S[fst a / x] B -> p /\ (fst a e. A /\ snd a e. C) |
||
28 |
G -> E. x x = fst a -> snd a e. S[fst a / x] B -> p /\ (fst a e. A /\ snd a e. C) |
||
29 |
G -> snd a e. S[fst a / x] B -> p /\ (fst a e. A /\ snd a e. C) |
||
30 |
G -> snd a e. S[fst a / x] B -> p /\ a e. Xp A C |
||
31 |
G -> a e. S\ x, B -> p /\ a e. Xp A C |